Crew resource management training in the intensive care unit. A multisite controlled before–after study. Issue 8 (3rd February 2016) - Kemper, Peter F; de Bruijne, Martine; van Dyck, Cathy; So, Ralph L; Tangkau, Peter; Wagner, Cordula
Abstract : Introduction: There is a growing awareness today that adverse events in the intensive care unit (ICU) are more often caused by problems related to non-technical skills than by a lack of technical, or clinical, expertise. Team training, such as crew resource management (CRM), aims to improve these non-technical skills. The present study evaluated the effectiveness of CRM in the ICU. Methods: Six ICUs participated in a paired controlled trial, with one pretest and two post-test measurements (after 3 and 12 months). Three ICUs received CRM training and were compared with a matched control unit. The 2-day classroom-based training was delivered to multidisciplinary groups (ie, ICU physicians, nurses, managers). All levels of Kirkpatrick's evaluation framework were assessed using a mixed method design, including questionnaires, observations and routinely administered patient outcome data. Results: Level I—reaction: participants were very positive directly after the training. Level II—learning: attitudes towards behaviour aimed at optimising situational awareness were relatively high at baseline and remained stable. Level III—behaviour: self-reported behaviour aimed at optimising situational awareness improved in the intervention group. No changes were found in observed explicit professional oral communication. Level IV—organisation: patient outcomes were unaffected. Error management culture and job satisfaction improved in the intervention group. Patient safety culture improved in both control and intervention units. Conclusions: We can conclude that CRM, as delivered in the present study, does not change behaviour or patient outcomes by itself, yet changes how participants think about errors and risks. This indicates that CRM requires a combination with other initiatives in order to improve clinical outcomes.